Univerza v Mariboru, Fakulteta za strojništvo - Polajnar, Andrej (2025)
University of Maribor, Faculty of Mechanical Engineering. The publication of the Faculty of Mechanical Engineering at the University of Maribor offers a comprehensive overview of the development, activities, and vision of one of Slovenia’s central technical institutions. In the introductory addresses by the editor, dean, and rector, reflections are shared on the significance of the faculty from the scientific, educational, and social point of view. The historical section highlights the key milestones in the faculty’s evolution, from its foundation to the present day, and introduces the leading figures – deans, vice-deans, and secretaries – who have guided its course. This is followed by an in-depth presentation of educational activities, scientific research and artistic work, as well as cooperation with industry and the wider community. Special attention is devoted to students, along with testimonies from graduates that reflect the experiences and values gained during their studies. The chapter on alumni links the past with the present and strengthens bonds across generations. The publication also presents administrative services and the infrastructural development of the faculty. Emphasis is placed on the contribution of the faculty’s coworkers to the creation of the University of Maribor’s academic insignia, underlining the faculty’s creative role in shaping the university’s identity. The concluding chapter looks ahead to the future – strategic goals and orientations for the period 2021–2030, together with detailed descriptions of the activities of laboratories and centres that represent the core of research excellence. Thus, the publication stands as a document of its time, a space for reflection, and a vision of the future – dedicated to students, staff, partners, and the broader public who together shape the story of the Faculty of Mechanical Engineering at the University of Maribor.
Keywords: University of Maribor; Faculty of Mechanical Engineering; history; development; activities; vision; 30 years